99.2k views
1 vote
Can some one pls Use elimination to solve each system of equations

2x - y = -1
3x - 2y = 1

User Likejudo
by
4.9k points

2 Answers

3 votes

Answer:

x= -3

y= -5

Explanation:

-2 (2x-y= -1) = -4x + 2y = 2

-4x + 2y = 2

3x - 2y = 1

-------------------

-x = 3

x = -3

plug the x= -3 into the equation to find y

User HarryM
by
5.9k points
4 votes

Answer:

Correct answer: x = - 3 and y = - 5

Explanation:

Given:

2 x - y = - 1

3 x - 2 y = 1

We will multiply first equation with number (- 2) and get:

- 4 x + 2 y = 2

then we add this equation to another and get:

- 4 x + 3 x = 2 + 1

- x = 3 / · (- 1)

x = - 3

now we replace x = - 3 in the first equation and get:

2 (- 3) - y = - 1 ⇒ - 6 - y = - 1 / ·(- 1) ⇒ 6 + y = 1 y = 1 - 6 = - 5

y =- 5

God is with you!!!

User Sathwick
by
5.2k points